DAMPAK KEPEMILIKAN LAHAN PADI SAWAH TERHADAP EFISIENSI TEKNIS DAN EFISIENSI LINGKUNGAN DI KABUPATEN ROKAN HULU - Defidelwina Defidelwina; Jamhari Jamhari; Lestari Rahayu Waluyati; Sri Widodo (AGRARIS: Journal of Agribusiness and Rural Development Research, 2019)
Land ownership, technical and environmental efficiency are interrelated aspects one another which influences the sustainability of farming. This study aims to estimate the impact of land ownership on the technical and environmental efficiency of wetland rice farming in the Rokan Hulu Regency. Data obtained from interviews with 100 farm households, and analyzed using the translog stochastic frontier production function estimated by the maximum likelihood method. This production function includes conventional and detrimental input (Nitrogen). The results showed that the average technical efficiency of farming was 84.8%. Meaning that farmers can increase their technical efficiency by 15.2%. While the average of environmental efficiency is 23.7%. It is recommended to farmers to reduce their detrimental inputs by 76.3%. The technical efficiency of landowners was lower than the tenant or sharing farmers. Otherwise, the environmental efficiency of landowners higher than tenant or sharing farmers.